2014
DOI: 10.1128/aem.03411-13
|View full text |Cite|
|
Sign up to set email alerts
|

Multistrain Probiotic Modulation of Intestinal Epithelial Cells' Immune Response to a Double-Stranded RNA Ligand, Poly(I·C)

Abstract: A commercially available product containing three probiotic bacterial strains (Lactobacillus helveticus R0052, Bifidobacterium longum subsp. infantis R0033, and Bifidobacterium bifidum R0071) was previously shown in animal trials to modulate both T H 1 and T H 2 immune responses. Clinical studies on this combination of bacteria have also shown positive health effects against seasonal winter diseases and rotavirus infection. The goal of this study was to use a well-established in vitro intestinal epithelial (HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 33 publications
3
40
0
2
Order By: Relevance
“…In this regard, we also reported that both B. infantis MCC12 and B. breve MCC1274 significantly reduced the expression of A20 in RVs-infected PIE cells (Figure 4) (50), which is in line with the capacity of both strains to improve IRF3 activation and IFN-β production. In line with our findings, MacPherson et al (64) also studied the effect of probiotics in the modulation of poly(I:C) induced inflammatory response in HT-29 cells. Stimulating HT29 cells with poly(I:C) alone increased the expression of A20, but the co-stimulation with poly(I:C) and probiotics significantly reduced A20 expression levels.…”
Section: Cellular and Molecular Mechanisms Of Immunobiotics Actionssupporting
confidence: 91%
“…In this regard, we also reported that both B. infantis MCC12 and B. breve MCC1274 significantly reduced the expression of A20 in RVs-infected PIE cells (Figure 4) (50), which is in line with the capacity of both strains to improve IRF3 activation and IFN-β production. In line with our findings, MacPherson et al (64) also studied the effect of probiotics in the modulation of poly(I:C) induced inflammatory response in HT-29 cells. Stimulating HT29 cells with poly(I:C) alone increased the expression of A20, but the co-stimulation with poly(I:C) and probiotics significantly reduced A20 expression levels.…”
Section: Cellular and Molecular Mechanisms Of Immunobiotics Actionssupporting
confidence: 91%
“…helveticus R0052 in a ratio of 20:20:60; respectively, and as described in MacPherson et al . [22]. To rehydrate the lyophilized bacteria for both single and multi-strain blend, 1 g was mixed for 15 min at room temperature (RT) in 99 mL of phosphate buffer [0.1% soy peptone (w/v), 0.121% K 2 HPO 4 (w/v), 0.034% KH 2 PO 4 (w/v)] as described in MacPherson et al .…”
Section: Methodsmentioning
confidence: 99%
“…and Audy et al . [22,27]. Briefly, bacterial pellet from 1 ml of this bacterial suspension was washed in PBS after centrifugation at 12800 x g for 10 min at room temperature (RT) and then re-suspended in serum-free RPMI-1640 media.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to Lactobacillus in mice can increase 2′5′-OAS activity and can up-regulate the expression of multiple OAS family members (Solis-Pereyra et al 1997;Weiss et al 2010). However, the opposite effect was observed in human intestinal cells, where a mixture of Lactobacillus and Bifidobacteria prevented the up-regulation of OASL and other antimicrobial genes during viral (dsRNA) exposure (MacPherson et al 2014). A single highly significant transcript from TMC6, which likely encodes a transmembrane channel protein (Mutai et al 2005), was also down-regulated in all comparisons involving the PBAFB group, suggesting that the interaction of PB and AFB 1 has suppressive effects not seen in the PB group.…”
Section: Pb and Immunosuppressionmentioning
confidence: 88%